Numerical Study on Laminar-Turbulent Transition Flow in Rectangular Channels of a Nuclear Reactor - Wang, Zhenying; Zhang, Rui; Yu, Ting; Liu, Zhiyun; Huang, Yu; Wang, Jianjun; Cong, Tenglong (Frontiers in Energy Research, 2020)
Laminar-turbulent transition flow can be observed in thermal engineering applications, but the flow resistance and heat transfer characteristics are not fully understood. In this work, flow and heat transfer for the laminar-turbulent transition in a rectangular channel were predicted by a four-equation transition turbulent model. A set of correlations for the heat transfer coefficient in a rectangular channel were developed and implemented in the RELAP5/MOD3.1 code to make it capable of analyzing a plate-type fuel assembly with rectangular coolant channels. The improved RELAP5/MOD3.1 code was employed to analyze the SBLOCA along with the SBO scenario for an integrated pressurized reactor, illustrating the effects of model modification on the evolution of the accident.